Верификация результатов численного исследования движения потока в проточной части регулирующего клапана паровой турбины - Бабаев, Артем Иванович; Голощапов, Владимир Николаевич (НТУ "ХПИ", 2016)
В статье представлены результаты численного исследования расходной характеристики регулирующего клапана части высокого давления турбины К-300-240 ПАО "Турбоатом". Рассмотрены поля газодинамических параметров в клапанном канале и получена величина приведенного расхода в зависимости от относительного подъема чаши клапана и относительного давления. Выполнено сопоставление полученных результатов расчетов с результатами соответствующих натурных экспериментов.

The improvement of the structure design of control valves using the contemporary methods of computational gas dynamics (CFD) requires the verification of used mathematical model, which is the top-priority problem. This scientific paper gives the comparison of the data of numerical investigation of the flow motion in the Venturi-type control valve in the high pressure section of the turbine К-300-240 with full-scale test data. A satisfactory agreement with experimental data with regard to the value of the reduced flow coefficient and the pressure distribution along the bypass of valve seat and valve cup has been shown. A relative error of the definition of reduced flow is within 10,2 % and for the average integral pressure distribution along the bypasses of valve seat and valve cup for all modes it is equal to 5 %. It has also been shown that the solution of problem in the axial symmetry statement gives an opportunity to significantly reduce the scope of computations, but it fails to provide an opportunity for taking into account in full the nonstationary effect of flow on actuated valve parts.
Verification of the data of numerical investigations of the flow motion in the control valve channel of steam turbine
Keywords: парораспределение; коэффициент расхода; РК; расчет газовой динамики; steam distribution; flow coefficient